Penerapan Media Video Pembelajaran pada Materi Cahaya dan Sifat-sifatnya di SD Negeri 003 Lubuk Sakat - Athallah, Naura Lulu Nadhifa; Tobing, Daniel Christopel Lumban (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
The implementation of the Merdeka Curriculum has reached most schools, one of which is at SDN 003 Lubuk Sakat. One of the differences between this curriculum and the previous curriculum is the learning of Natural Sciences (IPA) and Social Sciences (IPS) which are integrated into Natural and Social Sciences (IPAS). To achieve interactive and meaningful learning for students, the application of media in the form of learning videos was carried out in class V (five) SDN 003 Lubuk Sakat. This activity was carried out for one meeting in the second week of the odd semester on the material of light and its properties. The steps taken include licensing with UPT SDN 003 Lubuk Sakat, preparing materials in learning videos, and implementing teaching and learning activities with learning videos. The attitude of students was enthusiastic and became more confident in expressing their respective opinions. Quizzes at the end of the lesson in the form of C2 and C3 questions showed that students understood the material of light and its properties and its application in everyday life.